The Absence of the Space In-between – Travelling in the 16th and 17th Centuries (KULT_online, 2009)
Axel Gotthard's monograph In der Ferne. Die Wahrnehmung des Raums in der Vormoderne (In the distance. The perception of space in early modern times) examines travelogues from widely disparate 16th and 17th century authors. Gotthard's main focus lies on German and French sources, which he plumbs for spatial references that determine the construction of self and other, homeland, nature and travelling itself. He sees these initial findings as proof that people's spatial perception during the early modern era, which he describes as "a succession of finite points" (p. 157), differed from that of both medieval and modern times. In sum, the study presents a variety of questions and an exemplary sketch of how historiography could address them.